Cobalt, nickel, and iron complexes of 8-hydroxyquinoline-di(2-picolyl)amine for light-driven hydrogen evolution. Issue 47 (16th November 2017) - Carmo dos Santos, Nadia Alessandra; Natali, Mirco; Badetti, Elena; Wurst, Klaus; Licini, Giulia; Zonta, Cristiano
Abstract : Novel first-row transition metal complexes based on the 8-hydroxyquinoline-di(2-picolyl)amine ligand were prepared and tested as potential HECs in light-driven experiments. Abstract : Novel cobalt, nickel, and iron complexes based on the pentadentate 8-hydroxyquinoline-di(2-picolyl)amine ligand were synthesized and thoroughly characterized. X-ray structures of both the cobalt and iron complexes were also obtained, showing the tendency to adopt a pseudo-octahedral geometry by coordination of an additional sixth ligand. These metal complexes were then studied as potential hydrogen-evolving catalysts (HECs) under both electrochemical and light-driven conditions. In particular, two different photochemical systems were tested involving either Ru(bpy)3 2+ /ascorbic acid or Ir(ppy)2 (bpy) + /TEA sensitizer/sacrificial donor couples. The electrochemical results showed that these metal complexes may behave as competent HECs. However, under photochemical conditions, only the cobalt compound displayed substantial hydrogen-evolving activity in both ruthenium- and iridium-based systems. The nickel and iron complexes, on the other hand, exhibited appreciable photocatalytic activity only in the iridium-based photochemical system, while showing negligible hydrogen evolution ability when employed in the ruthenium-based one.